Bienestar subjetivo hedónico en una muestra de adolescentes de la zona rural y urbana de cinco municipios del Departamento del Tolima (2020)
Hedonic well-being is based on the notion that increased pleasure and decreased pain lead to happiness. Hedonic concepts are based on the notion of subjective well-being. Subjective well-being is a scientific term that is used specifically to refer to the "happy life or good life". It is an affective component (affects high positive and low low negative affect) and a cognitive component (life satisfaction). Likewise it is exposed that a happiness in the individual is experienced when the positive affect and the satisfaction with life are high. The objective of the present investigation is to evaluate the subjective cognitive and affective hedonic well-being of a sample of adolescents from the rural and urban areas of five municipalities in the department of Tolima, the present investigation work has an empirical analytical paradigm, where according to (Arnal, Del Rincón Y Latorre 1992), objectivity prevails over other elements. By participating in the principle of objectivity, the replicability of the investigations is assumed, therefore, the possibility of verifying or not, the knowledge generated. The sample is made up of 1309 adolescents of both sexes. Measurement scales (SWLS, SPANE, and SWI) were used. Taking all of the above into account, it is important to conclude the influence of different contexts in the constitution of subjective well-being of young people. Another aspect that is relevant is the comparison of the results obtained for the areas of residence, as it is possible to identify the urban area, it has greater results in relation to the satisfaction with the relative and the security of the context. Keywords: subjective hedonistic well-being, affection, adolescents